Efficacy of Urethral dilatation with Uttarbasti in the management of Recurrent Urethral Stricture-A Single Case Study - Kazi, Wasim; Kumar Sharma, Rajesh; Shah, Harshit; Sharma, Varsha; Panchal, Sonal (Asian Journal of Pharmaceutical Research and Development, 2023)
Urethral stricture disease is the common problem occurred in the patients after chronic urinary tract infection, urethral injury or post-surgical interventions performed through per urethra. In Ayurvedic literature urethral stricture may be correlated as mutrotsanga mentioned in Sushruta Samhita. There are advance surgeries available as the science advances with technology various surgeries like Urethroplasty, Visual Internal Urethrotomy, and Dilatation of urethra. The way to overcome this problem is surgery i.e. urethroplasty. But the recurrence rate is high enough to think the alternative. In this case study, 40 years old Male patient suffering from recurrent urethral stricture was came to Shalya Tantra OPD. Patient also undergone repeated urethral dilatations two times but not relieved. So after clinical examination and investigations the case diagnosed as urethral stricture and treated with Ayurvedic Para-surgical procedure i.e uttarbasti to avoid recurrent urethral stricture. In Ayurvedic literature Uttarbasti is the procedure in which some medicinal preparations are introduced per urethra. (As per reference given in sushruta samhita) Uttarbasti was done at 3 days interval for 4 weeks. In this particular study urethral dilatation done by urethral dilatators After that Uttarbasti has been given. After 3rd sitting patient got 70% relief. Thus we can conclude that uttarbasti can be considered as a golden choice of treatment for urethral stricture in Ayurved.